Profile communautaire jeunes et aînés : Populations anglophones Gaspé - Vision Gaspé-Percé Now (2016)
Ce document est une ressource pour les organismes communautaires et gouvernementaux et pour ceux qui peuvent bénéficier de l’information visant les aînés et les jeunes anglophones de Gaspé. La production du document est possible grâce au soutien financier de Santé Canada. Les données démographiques ont été fournies par le Réseau communautaire de santé et des services sociaux (RCSSS).

Building Community Capacity From Evidence to Action (2015-2016) : Profile of English-speaking Seniors : CSSS de La Côte-de-Gaspé - Pocock, Joanne (Seniors Action Quebec (SAQ), 2015)
The Seniors Action Québec (SAQ) project is designed to mobilize English-speaking (ES) seniors (65+) and their communities in four regions of the province (Gaspésie, Greater Quebec City, Outaouais and the North Shore). This will be done by creating a network among English language regional community organizations to amplify the voice of minority language seniors and enhance their contribution to the vitality of their communities. The project will ready the network to identify critical issues affecting English-speaking seniors, establish regional action plans to address seniors’ priorities and to generally promote awareness of provincial and regional organizations serving the interests of the 65 years and over age group.